2011
DOI: 10.1007/s11104-011-0885-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of active transport and transpiration on nickel and cadmium accumulation in the leaves of the Ni-hyperaccumulator Leptoplax emarginata: a biophysical approach

Abstract: Aims The primary aim of this study was to investigate the impact of active nickel and cadmium transport, transpiration and shoot biomass production on Ni and Cd accumulation in the leaves of the Ni-hyperaccumulator Leptoplax emarginata. A secondary objective was to observe the effects of various concentrations of nickel and cadmium in solutions on the plant growth and ecophysiological characteristics of these plants. Finally, the study sought to identify possible nickel and cadmium concentration gradients in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 65 publications
(67 reference statements)
2
3
0
Order By: Relevance
“…But, most of the solubilized Mg and Fe were leached in the percolated solution, with L. emarginata absorbing a very small part of these elements (about 9% and 6% (estimation), respectively) in comparison with Ni (88%). These results suggested that the strong ability to hyperaccumulate Ni by L. emarginata as reported in controlled conditions 5,37 could act on chrysotile dissolution by inducing a sharp decrease of water-soluble Ni in the rhizosphere. We could not exclude that the release of Fe and Mg (only provided by chrysotile in the system and necessary for plant development) influenced initial chrysotile weathering process.…”
Section: ■ Discussionsupporting
confidence: 61%
“…But, most of the solubilized Mg and Fe were leached in the percolated solution, with L. emarginata absorbing a very small part of these elements (about 9% and 6% (estimation), respectively) in comparison with Ni (88%). These results suggested that the strong ability to hyperaccumulate Ni by L. emarginata as reported in controlled conditions 5,37 could act on chrysotile dissolution by inducing a sharp decrease of water-soluble Ni in the rhizosphere. We could not exclude that the release of Fe and Mg (only provided by chrysotile in the system and necessary for plant development) influenced initial chrysotile weathering process.…”
Section: ■ Discussionsupporting
confidence: 61%
“…Similar phenomenon was found for the nickel (Ni) hyperaccumulator Leptoplax emarginata (Bartoli et al 2012). In contrast, a significantly positive relationship is observed between the shoot Cd concentration and the transpiration of Phytolacca americana (Liu et al 2010).…”
Section: Introductionsupporting
confidence: 68%
“…We propose that, unlike the Ni hyperaccumulator L. emarginata (Bartoli et al 2012) or Cd hyperaccumulator S. alfredii, for the As hyperaccumulator P. vittata with its large biomass (∼9 t dry weight h m −2 year −1 ), transpiration is the main upward translocation process for As after the reduction of As(V) to As(III). This study aims to verify this hypothesis by investigating the role of transpiration in the As hyperaccumulation.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, overabundance of Cd has been found to impede both shoot biomass and plant height in ornamental plants, as demonstrated by Liu et al [16] and Wu et al [17]. It is noteworthy that studies in wheat and Leptoplax emarginata have found that the transpiration rate affects plant height and shoot biomass, subsequently influencing the absorption of Cd [18,19]. This study aimed to examine the potential correlation between plant height and Cd accumulation in a sample of 31 tomato cultivars, and also to determine whether plants could influence Cd accumulation through physiological processes such as transpiration rate or photosynthesis.…”
Section: Introductionmentioning
confidence: 86%